2012
DOI: 10.1007/s00394-012-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of adipokines in connective tissue diseases

Abstract: ObjectiveTo discuss the relationship between adipokines and connective tissue diseases, by putting special emphasis on the potential role of leptin, adiponectin, resistin, and other adipose tissue products in the pathogenesis of rheumatoid arthritis and systemic lupus erythematosus and on possible application of adipokine-targeted therapy in the treatment of these disorders with emphasis on the recent findings.MethodsPubMed literature search complemented by review of bibliographies listed in identified article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 127 publications
(197 reference statements)
3
110
2
11
Order By: Relevance
“…Scotece et al (2012) [64] described the major effects of increased synovial and circulating levels of adiponectin in RA. [65] suggested that these different actions can be explained by different mechanisms: LMW adiponectin has anti-inflammatory activities, while the HMW adiponectin has proinflammatory activities. However, Frommer et al (2012) [66] showed a proinflammatory and destructive role of all isoforms Correlation between visfatin levels and disease activity and reduced levels after treatment.…”
Section: Adponectinmentioning
confidence: 99%
“…Scotece et al (2012) [64] described the major effects of increased synovial and circulating levels of adiponectin in RA. [65] suggested that these different actions can be explained by different mechanisms: LMW adiponectin has anti-inflammatory activities, while the HMW adiponectin has proinflammatory activities. However, Frommer et al (2012) [66] showed a proinflammatory and destructive role of all isoforms Correlation between visfatin levels and disease activity and reduced levels after treatment.…”
Section: Adponectinmentioning
confidence: 99%
“…Several researchers observed an increase in adiponectin concentration in SLE patients [57,91], while others did not ind differences compared to the control [50,58]. However, plasma adiponectin levels tend to be higher in patients with renal SLE in comparison to healthy controls and patients with nonrenal SLE [93].…”
Section: Adipocytokines and Their Relation To Atherosclerosis And Sysmentioning
confidence: 96%
“…It has been speculated that altered serum/plasma levels of adipokines in SLE might be related to coronary atherosclerosis, insulin resistance, and the inlammatory process [57]; however, these correlations need to be further explored and documented [65]. A deep insight into the mechanisms of adipokine actions would help develop new therapies-also for autoimmune disorders [58,66].…”
Section: Adipocytokines and Their Relation To Atherosclerosis And Sysmentioning
confidence: 99%
See 2 more Smart Citations